The ‘context’ of transport project cost performance: Insights from contract award to final construction costs - Love, Peter; Ika, L.A. (ELSEVIER SCI LTD, 2021)
Despite the plethora of studies examining the cost performance of transport projects, we still do not fully understand why they exceed their agreed price for construction. A lack of an in-depth exploration of context has contributed to this lack of understanding. In this paper, we seek to provide a context as to why the construction costs of transport projects experience increases from their contract award. We adopt sense-making approach, which is qualitative in nature, to examine the performance and financial reviews for eight transport projects constructed by an Australian contractor. The reviews are checkpoints undertaken during the construction of projects to monitor actual costs and forecasted profits for the contractor. The reviews are performed at the 50% and 75% milestones of a project's forecasted schedule by a team independent from the contractor's organization. We look into context states of projects such as their programme, quality, safety, design, and management. We use a context breakdown structure to uncover the ‘contexts within contexts’ that significantly contribute increases to construction costs. We reveal that the mean forecasted contractor margin was almost 9%, which reinforces the belief that there is a lack of competition in the marketplace. Overall, the hierarchy of contexts within contexts we unravel provides further understanding as to why transport projects experience increases in their construction costs. Considering the nature of the recurring contexts that we identify, we recommend that governments re-calibrate their approaches to procuring their transport projects. We suggest that they embrace negotiated contracts, alliance contracting, leadership and resourcing strategy, and work toward establishing a generative culture in the projects they procure.